On-site rapid and simultaneous detection of acetamiprid and fipronil using a dual-fluorescence lab-on-fiber biosensor - Song, Dan; Liu, Jiayao; Xu, Wenjuan; Han, Xiangzhi; Wang, Hongliang; Zhuo, Yuxin; Li, Chunsheng; Long, Feng (Mikrochimica acta (1966), 2022)
A dual-fluorescence lab-on-fiber biosensor was developed for the rapid and simultaneous on-site determination of acetamiprid and fipronil, based on time-resolved effect and indirect competitive immunoassay principle. The optical fiber modified with two hapten-protein conjugates serves as a bifunctional bio-probe. The dual-color fluorescent reporters were prepared via labeling acetamiprid and fipronil antibodies with Cy5.5 and Alexa Fluor 555, which were excited at 635-nm and 520-nm laser wavelengths, respectively. In the presence of targets, the binding sites of corresponding antibodies were occupied and less antibodies were connected to the probe surface, resulting in the reduction of fluorescence signal. The concentration of acetamiprid and fipronil was determined by measuring the fluorescence signals at 568 nm and 702 nm (emission wavelengths), respectively. Under optimal conditions, the linear response range was 14.2–225.4 ng/L for acetamiprid and 25.1–162.8 ng/L for fipronil, and the limit of detection was 6.51 ng/L and 17.8 ng/L for acetamiprid and fipronil, respectively. The method was successfully applied to the simultaneous detection of acetamiprid and fipronil in three environmental samples, and the recoveries were between 90 and 128%. The dual-fluorescence lab-on-fiber biosensor provides a feasible platform for simultaneous and rapid detection of multiple pesticide residues. Graphical abstract A dual-fluorescence lab-on-fiber biosensor was developed for the rapid and simultaneous on-site determination of acetamiprid and fipronil. A bifunctional bio-probe was prepared from the optical fiber modified with two hapten-protein conjugates. Acetamiprid and fipronil antibodies were labeled with different fluorophores and used as dual-color fluorescent reporters.